Portfolio Selection and Performance Evaluation Through Benjamin Graham’s Value Investing - Srivastava, Vinay K.; Kulshrestha, Nitin (Indian Journal of Finance and Banking, 2020)
Purpose: The objective of this study is to validate the value investing concerning filtering valued stock in the Indian stock market (Nifty 50) & United States (Dow Jones) during the period 2014 -20.Design /Methodologies/Approach:  We have selected the data of the National Stock Exchange and Dow Jones to apply the value investing technique for choosing the stocks and building a significant portfolio. Further, we compare the mean returns of B & H passive strategy. The empirical analysis includes the selected portfolio from Jan 2014 to May 2020.Results & Practical Implication: The mean return of portfolio selected by Value investing outperform as comparative to passive strategy, i.e. Buy & Hold strategy. The successful application of value investing will encourage the practitioners & academicians of financial markets to research & explore further uses & practical impact of the present study.JEL Classification Codes: F37.